2008
DOI: 10.1136/ard.2008.091074
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a distinctive pattern of bone formation in enthesophytes

Abstract: Entheseal new bone formation occurs by a combination of three methods of ossification. However, endochondral ossification was atypical and differed from that seen in the normal development of cartilage bones or during fracture healing. How the inflammatory process modulates these processes could lead to a better understanding of entheseal new bone formation in SpA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 13 publications
(14 reference statements)
7
93
1
4
Order By: Relevance
“…Bone formation at insertions occurs at sites of maximal entheseal tension and histologically may exhibit endochondral, intramembranous or chondroidal metaplasia [4]. The basis for the post inflammatory new bone formation at entheses in SpA remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Bone formation at insertions occurs at sites of maximal entheseal tension and histologically may exhibit endochondral, intramembranous or chondroidal metaplasia [4]. The basis for the post inflammatory new bone formation at entheses in SpA remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…2 On the other hand, Benjamin and McGonagle have thoroughly studied the age-related enthesophyte formation in the Achilles tendon in both rodents and humans. 4,5 Although obviously it remains unclear whether formation of syndesmophytes (which occur in the inflammatory context of AS) and enthesophytes (which may mainly result from mechanical factors during aging 6 ) follow the same molecular pathways, the Achilles tendon is also affected in AS in humans, 7 and is fundamentally similar to the entheses principally affected in AS. 4 Consequently, Benjamin et al 4,5 reasonably assumed that the mechanisms governing syndesmophyte formation in the spine and enthesophyte development in the Achilles tendon may be similar.…”
mentioning
confidence: 99%
“…24 In this hypothesis, cytokines may stimulate ectopic collagen calcification by the mere stimulation of TNAP activity, and this calcified matrix, may in turn induce the ossification process, in the arterial wall, 25 and in entheseal fibro-cartilage during AS. 4,5 MATERIALS AND METHODS Chemicals Cell culture plastic ware was purchased from D Dutscher (Brumath, France). Dulbecco's minimum essential medium (DMEM), a-MEM, fetal calf serum (FCS), insulin, L-glutamine, penicillin, streptomycin (P/S), trypsin/EDTA, and Extract-All reagents were from Eurobio (Les Ulis, France).…”
mentioning
confidence: 99%
“…Histological characteristics of the formation of the posterior osteophytes in spine as age advances has been documented in literature [22][23][24][25]. Reviewing the literature we found that Peng et al [26] in the experimental model of cervical spondylosis in rabbits had suggested that vertebral osteophytes arises from proliferation of peripheral articular cartilage which undergoes transformation into cartilaginous osteophytes and then converts into bony osteophytes through an endochondral calcification and ossification.…”
Section: Experimental Evidence Showing the Development Of The Posterimentioning
confidence: 86%